DISCRIMINATIVE CONTROL OF PUNISHED STEREOTYPED BEHAVIOR IN HUMANS - Doughty, Shannon S.; Anderson, Cynthia M.; Doughty, Adam H.; Williams, Dean C.; Saunders, Kathryn J. (Journal of the experimental analysis of behavior, 2007)
The purpose of this experiment was to establish discriminative control of responding by an antecedent stimulus using differential punishment because the results of past studies on this topic have been mixed. Three adults with mental retardation who exhibited stereotypy not maintained by social consequences (i.e., automatic reinforcement) participated. For each subject, stereotypy occurred frequently in the presence of a stimulus correlated with nonpunishment of stereotypy and rarely, if ever, in the presence of a stimulus correlated with punishment of stereotypy. Latency measures showed that the antecedent stimulus correlated with punishment served as the discriminative stimulus for the suppression of stereotypy. These results are important insofar as they show that discriminative control by an antecedent stimulus develops with punishment, and because it sometimes may be desirable to establish such control of socially inappropriate behavior.